The Self, Agency and Spatial Externalizations of Inner Verbal Thoughts, and Auditory Verbal Hallucinations - Stephane, Massoud (Frontiers in Psychiatry, 2019)
Background Auditory Verbal Hallucinations (AVH) are experienced as the “voices” of others (O-AVH) or self (S-AVH) in internal space/inside the head (IS-AVH) or external space (ES-AVH), and are considered to result from agency and spatial externalizations of inner speech. Both types of externalizations are conflated, and the relationship between these externalizations and AVH experiences is unclear. In this paper, I investigate the relationship between cognitive agency and spatial externalizations and between externalizations and the types of AVH experience. Method 25 patients with history of AVH and 24 matched healthy controls performed agency and spatial distinction tasks: distinction between self-generated (read) (S) sentences and other-generated (O) sentences, and between sentences read silently (experienced in internal space, IS) and sentences read aloud (experienced in external space, ES). Regression analyses between misattribution biases (S-O vs. IS-ES, and O-S vs. ES-IS) were obtained. t tests were used to compare misattribution biases between AVH subtypes (S-AVH vs. O-AVH, and IS-AVH vs. ES-AVH). Results Regressions suggest that agency distinction is independent from spatial distinction in both groups. O-AVH and S-AVH subgroups differed only with respect to S-O bias, and IS-AVH and ES-AVH subgroups differed only with respect to IS-ES bias. Conclusion These results suggest that agency and spatial externalizations of inner speech are independent at phenomenological and cognitive and levels; and that these externalizations are co-related across levels. I discuss the implications of these findings in the wider context of research on AVH on the experience of the self.